2016
DOI: 10.1242/jcs.183806
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-1 sorting in axons controls the differential retraction of arbor terminals

Abstract: The ability of neurons to generate multiple arbor terminals from a single axon is crucial for establishing proper neuronal wiring. Although growth and retraction of arbor terminals are differentially regulated within the axon, the mechanisms by which neurons locally control their structure remain largely unknown. In the present study, we found that the kinesin-1 (Kif5 proteins) head domain (K5H) preferentially marks a subset of arbor terminals. Time-lapse imaging clarified that these arbor terminals were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 63 publications
5
21
0
Order By: Relevance
“…Thus, KIF2A plays an important role in suppression of collateral branch extension, but a role in branch initiation was not observed. Similarly, a recent study found that Kinesin-1 (KIF5) accumulates at the tips of neurites within the axon arbor of cerebellar granule neurons and suppresses their retraction, resulting in stabilization and subsequent increased growth (Seno et al, 2016). Moreover, a role for microtubule motors in the formation of collateral branches along sensory axons in response to treatment with NGF is suggested by a study using ciliobrevin D, an inhibitor of the retrograde motor protein dynein (Sainath and Gallo, 2015).…”
Section: Cytoskeletal Dynamics and Reorganization Underlying The Earlmentioning
confidence: 99%
“…Thus, KIF2A plays an important role in suppression of collateral branch extension, but a role in branch initiation was not observed. Similarly, a recent study found that Kinesin-1 (KIF5) accumulates at the tips of neurites within the axon arbor of cerebellar granule neurons and suppresses their retraction, resulting in stabilization and subsequent increased growth (Seno et al, 2016). Moreover, a role for microtubule motors in the formation of collateral branches along sensory axons in response to treatment with NGF is suggested by a study using ciliobrevin D, an inhibitor of the retrograde motor protein dynein (Sainath and Gallo, 2015).…”
Section: Cytoskeletal Dynamics and Reorganization Underlying The Earlmentioning
confidence: 99%
“…Axonal processes with the motor domain of kinesin enriched at the terminals exhibit lower retraction rates. Furthermore, local inhibition of kinesin function by chromophore-assisted light inactivation increases the retraction rate of the target process but not that of the neighboring process [11]. These results suggest that a process-dependent difference in microtubule stability within a single arbor contributes to differential terminal retraction by regulating kinesin-mediated axonal transport.…”
Section: Microtubule Regulationmentioning
confidence: 84%
“…Among the various posttranslational modifications of tubulins, tyrosination and acetylation are affected by microtubule stability, that is, stable microtubules contain more detyrosinated and acetylated tubulins [27]. In axonal arbors, microtubules near growth cones are unstable and abundant with tyrosinated and deacetylated tubulins, whereas microtubules in longer processes are more stable than those in shorter processes at the region near the branch point [11,28,29]. Consistent with these observations, longer processes are more enriched with detyrosinated and acetylated microtubules than their neighboring shorter processes when compared at the same distance from the axonal branch point (Fig.…”
Section: Microtubule Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…During neuronal polarization, microtubule turnover becomes slower in longer axonal processes compared with minor processes 15 . When the microtubule turnover of arbor branch pairs is compared in the area proximal to the branching point, it is more stable in the longer process than in the shorter one 16 . Consequently, the ratio of dTyr and Ac of tubulin is higher in longer arbor processes.…”
mentioning
confidence: 99%